The role of halalan-toyyiban supply chain practices as significant predictors towards excellent customer service management / Anizah Zainuddin, Sarah Irdina Ridzwan and Sarah Batrisyia Ridzwan. - Zainuddin, Anizah; Ridzwan, Sarah Irdina; Ridzwan, Sarah Batrisyia (Universiti Teknologi Mara Selangor, 2020)
This study examines the role of Halalan-Toyyiban supply chain practices (HTSCP) in the context of service management. Investigation was done to see how retail customers react to the role of HTSCP; that later influence their overall grocery experience. Halalan Toyyiban is a process associated with religious belief and as such it would be difficult to control and guarantee. From the consumer point of view, the process is difficult to evaluate and verify even after consuming the product. Therefore, consumers have to largely rely on the retailer on the reliable information to guide their purchase. In the traditional context of supermarket retailing, excellent customer service management could be interpreted as just meeting the expectations of the supermarket customers, not any sort of exceeding or falling short of their expectations. It is only recently that several of the supermarkets try to achieve competitive advantage by taking the responses of their customers beyond the level of just service satisfaction. These supermarket retailers are now towards exceeding their service expectations. This study attempts to fill this gap by examining the relationship between the roles of HTSCP as significant predictors towards excellent customer service management. Structured questionnaires were distributed to 489 supermarket customers using purposive sampling technique in the urban area. The instruments used for data collection for all variables in the study include halal inputs, halal processes, controls for halal, halal outputs and excellent customer service management were adapted from Halalan- Toyyiban Assurance Pipeline (Management System Requirements for Retailing) of Department of Standards Malaysia as well as from various studies using a five-point Likert scale. The results suggest that all determinants of HTSCP had a good relationship with excellent customer service management. This study identifies additional management efforts that can be implemented in enhancing good retail supermarket practice.